(untitled) (International Seminar of Islamic Counseling and Education Series Proceeding, 2025)
This study aims to analyze the influence of social support on the stress levels experienced by out-of-town students in The Department of Islamic Education Guidance and Counseling at UIN Sultan Syarif Kasim Riau. Entering university as an out-of-town student is a transitional period filled with unique challenges that can be significant sources of stress, including cultural adaptation, financial independence, and academic pressure. Social support is theoretically viewed as a key protective factor against these stressors. Employing a quantitative approach with a correlational design, this study involved 27 out-of-town IEGC students selected through purposive sampling. Data were collected using a Likert scale questionnaire for both variables—social support (independent) and stress level (dependent)—and then analyzed with SPSS software. Data analysis included classical assumption tests (normality, linearity, heteroscedasticity) and hypothesis testing using simple linear regression analysis. The classical assumption tests confirmed that the data were normally distributed, had a linear relationship, and exhibited no heteroscedasticity. However, hypothesis test results showed that social support did not have a statistically significant effect on stress levels, with a significance value of p=0.190 (p>0.05). The R² value of 0.068 indicates that social support explained only 6.8% of the variance in stress levels. Consequently, the alternative hypothesis (Ha) was rejected. This non-significant result is likely due to methodological limitations, particularly the very small sample size which diminished the statistical power, as well as the possible presence of more dominant variables such as resilience and individual coping strategies that were not measured in this study